Photodynamic inactivation of methicillin-resistant Staphylococcus aureus by indocyanine green and near infrared light - Tak-Wah Wong; En-Chi Wu; Wen-Chien Ko; Ching-Chi Lee; Lien-I Hor; I-Hsiu Huang (Wolters Kluwer Medknow Publications, 2018)
Background: Antimicrobial photodynamic therapy (APDT) has become a potential regimen to treat multidrug-resistant bacterial infections. Limited data showed indocyanine green (ICG), a safe and inexpensive contrast medium for eye angiography and hepatic function examination, is an effective photosensitizer in APDT to kill methicillin-resistant Staphylococcus aureus (MRSA) after excitation with laser. Objective: We investigated the potentials of ICG-APDT with an inexpensive, non-coherent commercial near infrared (NIR) lamp against MRSA. Methods: The inhibition of MRSA was studied after exposing bacteria to NIR with different light doses and concentrations of ICG. The selectivity on MRSA was examined on human fibroblasts. Bacterial virulence including the activities of coagulase and enterotoxin was investigated. The effects of singlet oxygen scavengers (tryptophan and ascorbic acid) and H2O2 on cell survival were evaluated. The morphology of bacteria after PDT was observed by transmission electron microscopy. Results: ICG-PDT inhibited the growth of bacteria by 5 log (99.999% inhibition) with 200 J/cm2 at 65.5 mW/cm2 in the presence of 100 μg/mL ICG. Adding 0.1% H2O2 at a lower PDT dose (25 μg/mL ICG and 100 J/cm2) increased its efficacy by 5 log. This PDT dose was not toxic to human fibroblasts. PDT significantly reduced the level of bacterial virulence factors. The inhibition effects were decreased by tryptophan and ascorbic acid suggested singlet oxygen involved in the process. TEM showed severe non-selective cell destruction immediately after irradiation. Conclusion: The study reveals ICG-PDT has the potential to treat MRSA by using a clinical accessible NIR lamp and photosensitizer.